2020
DOI: 10.1128/aem.00525-20
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Engineering To Generate Plasmid-Free Phenylalanine- and Tyrosine-Overproducing Escherichia coli Strains That Can Be Applied in the Generation of Aromatic-Compound-Producing Bacteria

Abstract: ABSTRACT Many phenylalanine- and tyrosine-producing strains have used plasmid-based overexpression of pathway genes. The resulting strains achieved high titers and yields of phenylalanine and tyrosine. Chromosomally engineered, plasmid-free producers have shown lower titers and yields than plasmid-based strains, but the former are advantageous in terms of cultivation cost and public health/environmental risk. Therefore, we engineered here the Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…PEP is also consumed and converted to pyruvate in glycolysis [ 53 ]. In order to conserve PEP, we deleted the pykA and pykF genes encoding pyruvate kinases, and the triple deletion strain BTR16 produced 535.87 mg/L of l -phenylalanine, a 36.90% increase than strain BTR13, in consistent with previous reports [ 54 , 55 ]. l -Phenylalanine biosynthesis is negatively regulated by the repressor TyrR targeting the transcriptional expression of the aroG and aroF genes encoding 3-deoxy-arabino-heptulonate 7-phosphate (DAHP) synthase isoenzymes and the aroL gene encoding shikimate kinase [ 56 ].…”
Section: Resultssupporting
confidence: 88%
“…PEP is also consumed and converted to pyruvate in glycolysis [ 53 ]. In order to conserve PEP, we deleted the pykA and pykF genes encoding pyruvate kinases, and the triple deletion strain BTR16 produced 535.87 mg/L of l -phenylalanine, a 36.90% increase than strain BTR13, in consistent with previous reports [ 54 , 55 ]. l -Phenylalanine biosynthesis is negatively regulated by the repressor TyrR targeting the transcriptional expression of the aroG and aroF genes encoding 3-deoxy-arabino-heptulonate 7-phosphate (DAHP) synthase isoenzymes and the aroL gene encoding shikimate kinase [ 56 ].…”
Section: Resultssupporting
confidence: 88%
“…Also, the chorismate mutase is affected by a feedback inhibition by Phe or Tyr and, accordingly, tyrA fbr and pheA fbr mutated proteins have been created ( Turnbull and Morrison, 1990 ; Vincent et al, 2002 ; Lütke-Eversloh and Stephanopoulos, 2005 ; Zhou et al, 2010 ; Cao et al, 2016 ). Nowadays, the co-overexpression of both feedback-inhibition resistant E. coli enzymes is common to gain aromatics production, mostly in E. coli and yeast ( Báez-Viveros et al, 2004 ; Zhang et al, 2014a ; Rodriguez et al, 2014 , 2015 ; Wang et al, 2019 ; Koma et al, 2020 ), as well as in cyanobacteria ( Ni et al, 2018 ; Brey et al, 2020 ; Deshpande, Vue and Morgan, 2020 ). Additionally, in the literature another reaction has been reported as high flux controlling step ( Luttik et al, 2008 ; Takai A, Nishi R, Joe Y, 2009; Darmawi et al, 2012 ; Rodriguez et al, 2015 ; Xu et al, 2019 ), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae , E4P and PEP were not abundant and were pathway bottlenecks based on the results of carbon tracing and 13 C metabolic flux analysis [ 31 ] . Many studies have revealed that the overexpression of transketolase (TktA) and phosphoenolpyruvate synthase ( PpsA) effectively raised the intracellular pool of E4P and PEP [ 32 , 33 ]. In yeast, the 3-deoxyD-arabino-heptulosonate-7-phosphate (DAHP) synthase ( ARO4 / ARO3 ) catalyzes the first step to condense PEP and E4P to form DAHP.…”
Section: Resultsmentioning
confidence: 99%